Serotypes of Serratia marcescens from human infections - Irino, Kinue (1989)
290 Serratia marcescens strains, most of them isolated from cerebro spinal fluid (CSF) and blood cultures, were c1assified into 46 serotypes according to the serological identifications methods described by Le Minor and Pigache. Of 25 serotypes disclosed among 145 isolates from CSF, 06, 14:H12 and 06, 14:H4 were the predominant types, and accounted for over 70% of all the strains typed. Among blood isolates 65% of 102 strains fell into three serotypes, 06,14:HI2 06,14:H4 and 01:H7. In 1980, the serotype 01:H7 caused a nosocomial infection in an infantile hospital in São Paulo Municipality, involving children less than 1 year old. It has been verified that more than 73%,70% and 80% of all the strains isolated from CSF, blood, and stool, respectively, were from children between 0-5 years of age. Of 12 serotypes dis closcd among 38 strains isolated from stool, the 2 most frequenty isolated serotypes from LCR and blood cultures, 06,14:HI2 and 06,14:H4, were also the predomintant types suggesting a potential source for Serra tia marcescens outbreaks in nurseries.